The Antibacterial Effect of Cannabigerol toward Streptococcus mutans Is Influenced by the Autoinducers 21-CSP and AI-2 - Muna Aqawi; Ronit Vogt Sionov; Michael Friedman; Doron Steinberg (Biomedicines, 2023)
Bacteria can communicate through an intercellular signaling system referred to as quorum sensing (QS). The QS system involves the production of autoinducers that interact with their respective receptors, leading to the induction of specific signal transduction pathways. The QS systems of the oral cariogenic Streptococcus mutans regulate the maturation of biofilms and affect its virulent properties. We have previously shown that the non-psychoactive compound cannabigerol (CBG) of the Cannabis sativa L. plant has anti-bacterial and anti-biofilm activities towards S. mutans. Here we were interested in investigating the effect of the two QS systems ComCDE and LuxS on the susceptibility of S. mutans to CBG and the anti-QS activities of CBG. This was assessed by using various comCDE and luxS mutant strains and complementation with the respective autoinducers, competence stimulating peptide (CSP) and (S)-4,5-dihydroxy-2,3-pentandione (DPD, pre-AI-2). We found that S. mutans comCDE knockout strains were more sensitive to the anti-bacterial actions of CBG compared to the WT strain. Exogenously added 21-CSP prevented the anti-bacterial actions caused by CBG on the ΔcomC, ΔcomE and ΔluxS mutants, while having no effect on the susceptibility of the WT and ΔcomCDE strains to CBG. Exogenously added DPD increased the susceptibility of WT and ΔluxS to CBG. Vice versa, CBG significantly reduced the 21-CSP-induced expression of comCDE genes and ComE-regulated genes and suppressed the expression of luxS with concomitant reduction in AI-2 production. DPD induced the expression of comCDE genes and ComE-regulated genes, and this induction was repressed by CBG. 21-CSP alone had no significant effect on luxS gene expression, while ΔcomCDE strains showed reduced AI-2 production. In conclusion, our study shows that the susceptibility of S. mutans to CBG is affected by the ComCDE and LuxS QS pathways, and CBG is a potential anti-QS compound for S. mutans. Additionally, we provide evidence for crosstalk between the ComCDE and LuxS QS systems.